The parade : a novel - Eggers, Dave (Alfred A. Knopf, 2019)
"From the best-selling author of The Monk of Mokha, a spare, powerful story of two men, Western contractors sent to work far from home, tasked with paving a road to the capital in a dangerous and largely lawless country. Four and Nine are partners, working for the same company, sent without passports to a nation recovering from ten years of civil war. Together, operating under pseudonyms and anonymous to potential kidnappers, they are given a new machine, the RS-90, and tasked with building a highway that connects the country's far-flung villages with the capital. Four, nicknamed the Clock, is one of the company's most experienced operators, never falling short of his assigned schedule. He drives the RS-90, stopping only to sleep and eat the food provided by the company. But Nine is an agent of chaos: speeding ahead on his vehicle, chatting and joking with locals, eating at nearby bars and roadside food stands, he threatens the schedule, breaks protocol, and endangers the work that they must complete in time for a planned government parade. His every action draws Four's ire, but when illness, corruption, and theft compromise their high-stakes mission, Four and Nine discover danger far greater than anything they could pose to each other"--